Negotiating the Challenges of a Calling: Emotion and Enacted Sensemaking in Animal Shelter Work - Schabram, Kira; Maitlis, Sally (Academy of Management Journal, 2017)
An important and underexamined issue in the study of callings concerns the challenges people face in pursuing a calling and how they negotiate those challenges. This process may be especially intense and consequential because callings involve work that is rooted in people’s values and that matters a great deal to them. Drawing on narrative interviews with 50 animal shelter workers, we identify three different “calling paths” that evolve as employees respond to the challenges they encounter. While all individuals in our study entered animal shelter work with similar passion and purpose, and faced similar kinds of challenges, those on different paths interpreted challenges differently, had different emotional responses to them, engaged in different kinds of enacted sensemaking, and developed different accounts of themselves and their guiding purpose, through which they interpreted subsequent challenges. The result was the emergence of three increasingly divergent calling paths over time, culminating in different emotional, psychological, and behavioral outcomes. Based on these findings, we develop a model of the recursive process through which individuals negotiate the challenges of a calling, contributing to the literatures on callings and employee responses to workplace challenges.